Pelatihan Kecakapan Hidup Optimalisasi Layanan Administrasi Desa berbasis Web inovasi Smart Village (Aplikasi Sideka ) - armida, armida; Sarianti, Rini; Iswari, Mega; Afdal, Zul (Universitas Negeri Padang, 2024)
The flagship program of Pariaman City is Smart Village. An effort to increase knowledge and awareness of the importance of managing correspondence and document management in marketing local products, the solution provided to the target audience, namely all administrators in the North Pariaman District, Pariaman City, is through life skills training for Optimizing Village Administration Services based on the Smart Village innovation Web. The method of this Community Service activity is in the form of training and assistance to village community servants, Bumdes/bunag, UMKM actors and togama in North Pariaman so that it is hoped that community servants will be able to manage e-documents and standard correspondence as a reference for villages in North Pariaman in improving the quality of public services to end users in a smart way. The final result of this activity is an increase in partner understanding in utilizing sideka technology in village administration services (e-administration), increasing community participation in promoting local products that meet e-Business standards. The sideka design which is equipped with a guide can be used as a model for developing an e-document and business information system in a smart way in Pariaman.